Bioactive Anti-Aging Substances: Geroprotectors - Anna D. Fokina; Anna D. Vesnina; Anna S. Frolova; Darya Yu. Chekushkina; Larisa A. Proskuryakova; Larisa M. Aksenova (Техника и технология пищевых производств)
People are constantly exposed to adverse environmental factors that affect their health. If combined with hereditary predisposition, they may lead to gerontological changes that reduce healthy and working life expectancy. Some measures can prevent premature aging, e.g., a balanced diet or biologically active anti-aging substances also called geroprotectors. This article reviews biologically active geroprotectors with a view to select promising components for novel biologically active additives and functional foods. The review covered five years of Russian research articles and patents on biologically active anti-aging agents indexed in the National Center for Biotechnology Information, ScienceDirect, eLIBRARY.RU, and the database of the Federal Institute of Industrial Property. The domestic market demonstrates a growing demand for biologically active supplements: in 2023, it increased by 10% in value terms as consumers’ interest in a healthy and long life continues to grow. The review also included quality criteria for biologically active anti-ageing agents, e.g., such plant metabolites as vitamins, polyphenols, antioxidants, adaptogens, peptides, etc. Thymalin, epithalamin, dasatinib, and epithalon are available on the domestic market. The list of potential anti-aging agents includes ethylamine, carnosine, glutathione, ubiquinone, curcumin, rutin, quercetin, resveratrol, senolytics, and sirutins. These biologically active substances prevent oxidative stress, accumulation of lipofuscin, and senescent cells. The most effective anti-aging agents come from Vitis amurensis, Rhodiola rosea, Schisandra chinensis, Galega officinalis, Eleutherococcus senticosus, Withania somnifera, and Panax ginseng.